All‐Inorganic Perovskite Nanocrystals: Microscopy Insights in Structure and Optical Properties. Issue 16 (25th June 2018) - de Weerd, Chris; Gregorkiewicz, Tom; Gomez, Leyre
Abstract: The all‐inorganic perovskite nanocrystals are recently in the research spotlight because of their potential use in photovoltaic and optoelectronic applications, partly thanks to their excellent optical properties and low‐cost production. This progress report focuses on the performance and characteristics of individual all‐inorganic perovskite nanocrystals from a microscopy point of view. High resolution techniques enable the characterization of this promising material on the microscale, providing information concerning individual nanocrystals. Abstract : All‐inorganic perovskite semiconductor nanocrystals are characterized by bright, tunable emission, and fast radiative recombination rates with high photoluminescence efficiencies. Here, their extraordinary properties, as revealed by microscopic techniques, are reviewed and summarized. The authors conclude that these nanocrystals are ideally suited to serve as building‐blocks to create ultrathin nanolayers and purposefully designed quantum‐structures.